'All was not well with the soldiers' diet': an evaluation of the effectiveness of official Australian Imperial Force food provisions, 1914–18. Issue 3 (1st September 2020) - Reynaud, Daniel
ABSTRACT: Official army rations were calculated to maintain the soldiers of the Australian Imperial Force (AIF) of 1914–1918 in good fighting trim. This article systematically investigates for the first time this provisioning, evaluating its effectiveness in sustaining the soldiers as fighting men. Three key unresolved areas of research are explored: the debate over whether army provisioning was more diverse and balanced than popular impressions, the degree to which conclusions drawn about provisioning at Gallipoli can be applied across all the campaigns of the AIF, and comparisons with British army provisioning. It concludes that AIF rations were physiologically and emotionally inadequate throughout the war.